2010
DOI: 10.1007/s10453-010-9182-y
|View full text |Cite
|
Sign up to set email alerts
|

The air spora of an orchid greenhouse

Abstract: The orchid collection of the ELTE Botanical Garden, Budapest, Hungary was monitored for airborne fungi using viable and non-viable air-sampling methods (Hirst-type and a 3-stage Andersen sampler) with three different culture media. A new culture method was also applied to identify fungal spores from Hirst-type samples. The aim of this study was to determine the diversity, human-and phytopathological potential of the air spora. To find out sources of airborne fungi, samples were collected from the air in an adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Penicillium and Cladosporium were the most frequently detected fungal genera in the present study, supporting findings from other greenhouse environments ( Davies et al , 1988 ; Monsó et al , 2002 ; Radon et al , 2002 ; Okushima et al , 2004 ; Li and LaMondia, 2010 ; Magyar et al , 2011 ). Penicillium spp.…”
Section: Discussionsupporting
confidence: 91%
“…Penicillium and Cladosporium were the most frequently detected fungal genera in the present study, supporting findings from other greenhouse environments ( Davies et al , 1988 ; Monsó et al , 2002 ; Radon et al , 2002 ; Okushima et al , 2004 ; Li and LaMondia, 2010 ; Magyar et al , 2011 ). Penicillium spp.…”
Section: Discussionsupporting
confidence: 91%
“…It is known to be part of fungal communities in many foods as wheat bran (Tan cinová & Labuda, 2009) and stored apple fruits (Granado et al, 2008), and in cheeses, as the Norvegia and Jarlsberg semi-hard cheeses (Kure & Skaar, 2000). Interestingly, it has already been isolated from a brine solution used for olives (Nisiotou, Chorianopoulos, Nychas, & Panagou, 2010) E. scoparia is an airborne endophytic mould, frequently isolated among the airspora of greenhouses, and pathogenic for some plant species (Magyar et al, 2011). It is a producer of several molecules (piramanes diterpenes and cytochalasins) whose antibiotic activity against some bacteria (Staphylococcus aureus ATCC 25923) and fungi (Microsporum gypseum) is being evaluated (Isaka, Palasarn, Prathumpai, & Laksanacharoen, 2011;Pongcharoen, Rukachaisirikul, Phongpaichit, Rungjindamai, & Sakayaroj, 2006).…”
Section: Mould Mycobiota From the Taleggio Cheese Environmentmentioning
confidence: 97%
“…The modification of the Hirst method made it easy to observe, identify and count the microconidia in air samples. Such modifications may give a deeper insight into the airborne dispersal of the studied fungus (Magyar et al 2006(Magyar et al , 2011. No significant difference was found between the spore concentrations measured at 10 and 150 cm, so it can be concluded that it is sufficient to monitor airborne Fusarium microconidia at a single sampling height.…”
Section: Discussionmentioning
confidence: 62%